Mulheres distintas : produção e reprodução dos significados da beleza feminina no campo de serviços estéticos - Roling, Liciane (2014)
The purpose of this dissertation is to investigate the production and reproduction of meanings of feminine beauty. Beauty is analyzed as a cultural phenomenon that influences the consumption behavior of women in society as well as feed a market worth billions chords, and Brazil holds an outstanding position worldwide. This phenomenon is investigated from the concepts of field and habitus proposed by Pierre Bourdieu. Under this interdisciplinary theoretical perspective the constitution of the field came from the identification of active agents in the production and reproduction of meanings of women's beauty, as well as their elements illusio, doxa and nomos . The research is based on qualitative methods and the data were collected through in-depth interviews with 25 field's agents beyond participant observation developed during the period of 3 months in 10 institutions that are part of the field of aesthetic services. Data were analyzed using critical discourse analysis. The dynamics of the field proved to be a game where individuals use their capital as a kind of chips in order to win field's prize. As a result it was highlighted that women seek beauty in order to devote itself not only with the advantages derived from the physical aspects, but to win the set of attributes inherent to this adjective, encouraging personal success. The consumers do this through the consumption of aesthetic services linking structure and amount of certain capital recovered in the field of aesthetic services.